1990
DOI: 10.1142/s012908359000013x
|View full text |Cite
|
Sign up to set email alerts
|

Dating Rock Varnishes by the Cation Ratio Method With Pixe, Icp, and the Electron Microprobe

Abstract: The measurement of rock varnish cation-ratios [(K+Ca)/Ti] and barium is evaluated by analyzing the same varnish scrapings with PIXE, inductively coupled plasma, neutron activation and wavelength dispersive electron microprobe. Results among these different methods are generally similar for ratios, but absolute concentrations differ in part due to uncertainties associated with weighing small samples. Barium concentrations are typically less than 1 % by weight; higher concentrations can be found in varnishes wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
37
1

Year Published

1995
1995
2020
2020

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 0 publications
5
37
1
Order By: Relevance
“…New York varnishes display the same sub-micron cross-sectional texture of layering imposed by clay minerals, contain clay minerals as seen in HRTEM imagery, and host a variety of microbial forms that are enhanced in Mn in in situ EDS observations. There are dozens of elements enhanced in arid varnish over background values (Bard et al, 1978;Dorn et al, 1990;Lakin et al, 1963;Nowinski et al, 2010), including the zinc and barium observed here. However, rhenium enhancement has not been observed previously in arid varnishes.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…New York varnishes display the same sub-micron cross-sectional texture of layering imposed by clay minerals, contain clay minerals as seen in HRTEM imagery, and host a variety of microbial forms that are enhanced in Mn in in situ EDS observations. There are dozens of elements enhanced in arid varnish over background values (Bard et al, 1978;Dorn et al, 1990;Lakin et al, 1963;Nowinski et al, 2010), including the zinc and barium observed here. However, rhenium enhancement has not been observed previously in arid varnishes.…”
Section: Discussionmentioning
confidence: 48%
“…While Mn and Ba often display a spatial autocorrelation at the micron scale, this is not always the case. In other varnishes collected from arid regions, barium does not appear to be correlated with Mn (Dorn, 2007;Dorn et al, 1990;Krinsley et al, 1990).…”
Section: Trace Element Enhancement: Zinc Barium and Rheniummentioning
confidence: 72%
“…The network was active when the Q 3 surface was active, but not afterwards. The glacial deposits of the northern Owens Valley generally consist of three major post-Bishop Tuff moraine systems, recording extensive glaciation within the last 200 ka (Gillespie, 1988;Dorn et. al., 1990;Phillips et al, 1990).…”
Section: Methodsmentioning
confidence: 99%
“…Only accurate field mapping and (Sharp and Birman, 1963) or Casa Diablo (Curry, 1971). d Minimum radiocarbon age on till from rock varnish (Dorn et al, 1987). e Minimum ages provided by accumulation of 26-Al and 10-Be in till boulders (Nishiizumi et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…g Rock varnish cation-ratio analysis providing minimum ages (Dorn et al, 1990). Tioga age from site #24 of Dorn et al (1990) (Table 1).…”
Section: Introductionmentioning
confidence: 99%